Therapeutic Effects of Probiotic Minas Frescal Cheese on the Attenuation of Ulcerative Colitis in a Murine Model - Cordeiro, Bárbara F.; Alves, Juliana L.; Belo, Giovanna A.; Oliveira, Emiliano R.; Braga, Marina P.; da Silva, Sara H.; Lemos, Luisa; Guimarães, Jonas T.; Silva, Ramon; Rocha, Ramon S.; Jan, Gwénaël; Le Loir, Yves; et al. (Frontiers in Microbiology, 2021)
Inflammatory bowel diseases (IBD) constitute a group of disorders that severely affect the gastrointestinal tract and may lead to an irreversible impairment of its structure and function. Ulcerative Colitis (UC), the most common form of IBD, is characterized by severe inflammation of the human colon. Probiotic bacteria have been studied as adjuvants to the treatment or prevention of IBDs. The selected probiotic strain Lactococcus lactis NCDO 2118 (L. lactis NCDO 2118) exhibits immunomodulatory effects, with promising results in the context of UC induced by dextran sodium sulfate (DSS), in mice models. Additionally, cheese is a dairy food that presents high nutritional value, besides being a good delivery system that can be used to improve survival and enhance the therapeutic effects of probiotic bacteria in the host. Therefore, this work investigated the probiotic therapeutic effects of an experimental Minas Frescal cheese, containing L. lactis NCDO 2118, in DSS-induced colitis in mice. During colitis induction, mice that consumed the probiotic cheese exhibited reduced severity of colitis, with attenuated weight loss, lower disease activity index, limited shortening of the colon length, and reduced in the histopathological score. Moreover, probiotic cheese administration increased gene expression of tight junctions’ proteins zo-1, zo-2, ocln, and cln-1 in colon and increase IL-10 release in the spleen and lymph nodes. In this way, this work demonstrates that consumption of probiotic Minas Frescal cheese, containing L. lactis NCDO 2118, prevents the inflammatory process during DSS-induced colitis in mice, opening perspectives for the development of probiotic functional foods for personalized nutrition in the context of IBD.